Deconditioning and Physical Fitness: Implications for Healthy School-Aged Children - Dhwani Chanpura (Medical Science: Trends and Innovations Vol. 6, 2025)
Background: Physical inactivity (PI) and sedentary behaviors (SB) are significant contributors to various health-related risks and the development of chronic diseases. With the rise of technology and screen time, children are spending increasingly more time engaged in sedentary activities, leading to a decline in physical fitness levels. Methodology: This observational study aimed to assess the physical fitness levels of 119 schoolchildren aged 11-16 years. The children were randomly selected and underwent baseline assessments followed by a battery of physical fitness tests. Results: The results showed significant reductions in fitness levels when compared to age-matched peer groups. Gender differences were observed, with girls performing better in flexibility tests, while boys excelled in muscular endurance and core strength tests. Overall, both boys and girls demonstrated lower fitness levels than expected for their age group (P-value is less than 0.05). Discussion: These findings highlight the negative impact of physical inactivity and sedentary behavior on children’s health. The study suggests a need for schools to integrate regular physical activity sessions into their daily schedules to improve physical fitness. Conclusion: Emphasizing physical education and activity can help children develop healthier habits and combat the growing issue of reduced physical fitness in the school-age population.